Design of a Long Distance Wi-Fi network for the populated centers of Peru, to reduce the digital divide and times of national emergency such as Covid-19 in rural areas. (LACCEI, 2024)
The present work contains a brief description of the main considerations required to carry out the deployment of a telecommunications network that mainly benefits the educational institutions of the populated centers of Peru through the use of Wi-Fi technologies for long distances which proposes low costs and greater benefits for a low-income population. A design is proposed based on data and information collected in the field from 22 populated centers in northern Peru. The design establishes the fundamental aspects for the deployment of the project, required capacity for the network, technical specifications of the equipment, topology of the wireless network, as well as a coverage analysis and the feasibility of each link, to finally estimate the most appropriate educational platform in times of crisis such as the Covid-19 pandemic and the reduction of the digital divide in areas of difficult access.